Samorządy dużych polskich miast wobec recentralizacji – postawy i ich uwarunkowania. Studium okresu 2015–2023 - Wirginia Aksztejn; Łukasz Mikuła; Marta Lackowska (Studia Regionalne i Lokalne)
In the article, we analyse the reactions of large Polish cities (over 100,000 inhabitants) to the (re)centralisation pressure of the central government in 2015–2023. Referring to the developed typology of these reactions, we attempt to measure the intensity of contestation on the part of cities and determine the variables that build the potential for expressing such contestation. As measures of contestation, we use three variables: the city mayor’s participation in the Self-Government Movement “Yes! For Poland”, the adoption of a local in vitro programme and the presence of a roundabout, square, or street named after Women’s Rights in the city. The independent variables were the city’s size and wealth, the city mayor’s political affiliation, and the local electorate’s political preferences. The study showed that the city’s size and its citizens’ political preferences are the factors most strongly associated with the tendency to engage in conflictual behaviour towards government policies.